A novel Pyrin-Associated Autoinflammation with Neutrophilic Dermatosis mutation further defines 14-3-3 binding of pyrin and distinction to Familial Mediterranean Fever. Issue 12 (23rd August 2017) - Moghaddas, Fiona; Llamas, Rafael; De Nardo, Dominic; Martinez-Banaclocha, Helios; Martinez-Garcia, Juan J; Mesa-del-Castillo, Pablo; Baker, Paul J; Gargallo, Vanessa; Mensa-Vilaro, Anna; Canna, Scott; Wicks, Ian P; Pelegrin, Pablo; et al.
Abstract : Objective: Pyrin-Associated Autoinflammation with Neutrophilic Dermatosis (PAAND) is a recently described monogenic autoinflammatory disease. The causal p.S242R MEFV mutation disrupts a binding motif of the regulatory 14-3-3 proteins within pyrin. Here, we investigate a family with clinical features consistent with PAAND in whom the novel p.E244K MEFV mutation, located in the +2 site of the 14-3-3 binding motif in pyrin, has been found. Methods: Multiplex cytokine analyses were performed on p.E244K patient and control serum. Peripheral blood mononuclear cells were stimulated ex vivo with lipopolysaccharide (LPS). In vitro, inflammasome complex formation was evaluated by flow cytometry of Apoptosis-associated Speck-like protein containing a Caspase recruitment domain (ASC) specks. Interleukin-1β (IL-1β) and IL-18 production was quantified by ELISA. The ability of the p.E244K pyrin mutation to interact with 14-3-3 was assessed by immunoprecipitation. Results: PAAND p.E244K patient serum displayed a different cytokine profile compared with patients with Familial Mediterranean Fever (FMF). In overexpression models, p.E244K pyrin was associated with decreased 14-3-3 binding and increased ASC speck formation. THP-1 monocytes expressing PAAND pyrin mutations demonstrated spontaneous caspase-1-dependent IL-1β and IL-18 secretion, as well as cell death, which were significantly greater than those of wild-type and the FMF-associated mutation p.M694V. Conclusion: In PAAND, disruption of the +2 position of a 14-3-3 binding motif in pyrin results in its constitutive activation, with spontaneous production of IL-1β and IL-18, associated with inflammatory cell death. The altered serum cytokine profile may explain the different clinical features exhibited by PAAND patients compared with those with FMF.